Influence of the cooling rate on the structure and mechanical properties of a cast alloy of Al-Mg-Si system - Mordovets, N.M.; Milman, Yu.V.; Korzhova, N.P.; Legka, T.N.; Kuprin, V.V.; Podrezov, Yu.N.; Grinkevych, K.E.; Voskoboinik, I.V.; Melnik, V.H. (Інститут проблем матеріалознавства ім. І.М. Францевича НАН України, 2009)
An investigation of influence of the cooling rate on the structure and hardness of a new cast eutectic (α-Al + Mg2Si) alloy of the Al—Mg—Si ternary system showed that the critical cooling rate at which a colonial eutectic structure disappears is ~10^5 K/s. The change-over from laboratory castings with a weight of 200g to commercial castings with a weight of 20 kg practically does not influence on the level of mechanical properties under comparable cooling conditions.